СОВЕРШЕНСТВОВАНИЕ СПОСОБОВ РЕАЛИЗАЦИИ РЕЛЕЙНОЙ ЗАЩИТЫ СИСТЕМ СБОРНЫХ ШИН РАСПРЕДЕЛИТЕЛЬНЫХ УСТАНОВОК - Ниценко, В.В.; Кулагин, Д.А. (Інститут електродинаміки НАН України, Київ, 2017)
The article analyzes all disadvantages of differential busbar protection and known methods of possible realization of their phase-differential protection. The authors improved more advanced methods for comparing current phases by phase-differential busbar protection, in particular, logical operations for each proposed method are given, including verification conditions that are required to ensure reliable start and trip from protection when identifying the emergency condition of internal fault, and also illustrations of the protection oparation are given when using each of these methods in case of internal and external faults. The choice of the most expedient method for comparing the currents phases for its subsequent implementation by the phase-differential protection device was made on the basis of building their comparative characteristics based on the results of theoretical and practical studies of the protection operation in emergency conditions. Conclusions were made about the advantages of using the proposed phasedifferential algorithm of relay busbar protection operation. References 10, figures 5, table 1.